Effect of 50% ethanolic extract of roots of Cissampelos pareira on some bio-chemical parameters to investigate the hepato-protective study in animal model (Rats) - Middha*Vinay Kumar1, Dr. Anil (Journal of Biomedical and Pharmaceutical Research, 2016)
In phytotherapeutic approach, the emphasis is on the development of a new drug whose extraction and fractionation have emanated on the basis of therapeutic activity. Cissampelos pareira Linn. (C. microcarpa, De Candolle) is a very variable, lofty, slender, dioecious, perennial, climber commonly distributed throughout topical and sub topical India, ascending up to an altitude of c 2,000m. The plant is very common in orchards, hedges, parks and gardens on moist soils, either creeping or twining around other plants. The roots of Cissampelos pareira (L.) Hirsuta (Menispermaceae) were collected and extracted with 50% ethanol solution. The selected plant extract was subjected for the preliminary acute toxicity studies in mice at different dose levels up to 2000 mg/kg. The results showed no abnormal symptoms either p.o or i.p and cause no mortality. Before the actual LD50 determination, a pilot study was made on a small group of mice mainly to select the dose ranges for the subsequent study. The 50% ethanolic extract of Cissampelos pareira were taken at various dose levels (200, 500, 1000, 1500, 2000 mg/kg b.wt.) dissolved in 1 % carboxymethyl cellulose administered orally to pairs of mice per dose level. The value of probability less than 5% (P < 0.05) was considered statically significant. Histological architecture of the C. pariera treated liver samples showed the ability of the C. papeira to prevent hepatocellular necrosis. In conclusion, the antitubercular drugs (isoniazid and rifampicin)-induced alterations on protein metabolism and hepatic antioxidant defense system were normalized by Cissampelos pareira co-administration, indicating a possible cytoprotective role of Cissampelos pareira against drug induced hepatotoxicity. Thus our studies give scientific evidences to support this plant’s traditional uses as claimed in folklore medicine. It was concluded from the results that the alcoholic extract of Cissampelos pareira (L.) possesses hepato-protective effect in experimental animals Key words: Cissampelos pareira Linn, C. pariera,dioecious